2011
DOI: 10.2139/ssrn.1910031
|View full text |Cite
|
Sign up to set email alerts
|

The Food Crises and Political Instability in North Africa and the Middle East

Abstract: Social unrest may reflect a variety of factors such as poverty, unemployment, and social injustice.Despite the many possible contributing factors, the timing of violent protests in North Africa and the Middle East in 2011 as well as earlier riots in 2008 coincides with large peaks in global food prices. We identify a specific food price threshold above which protests become likely. These observations suggest that protests may reflect not only long-standing political failings of governments, but also the sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 21 publications
4
134
0
4
Order By: Relevance
“…This growing body of research has evidenced a link between the natural environment and instability [35] and an increase in the occurrence and intensity of intra-state conflict. In particular, climate change [41][42][43][44][45], resource scarcity [3,[46][47][48][49][50][51][52][53][54] and prices of food [3,45,[55][56][57][58][59][60][61] have been highlighted as stressors or catalysts for conflict or, more generally, as a threat for a country's national security.…”
Section: Introductionmentioning
confidence: 99%
“…This growing body of research has evidenced a link between the natural environment and instability [35] and an increase in the occurrence and intensity of intra-state conflict. In particular, climate change [41][42][43][44][45], resource scarcity [3,[46][47][48][49][50][51][52][53][54] and prices of food [3,45,[55][56][57][58][59][60][61] have been highlighted as stressors or catalysts for conflict or, more generally, as a threat for a country's national security.…”
Section: Introductionmentioning
confidence: 99%
“…The wave of social unrest known as the Arab Spring was preceded by food riots, the result of spiking global food prices. In turn, the cause of the fluctuations in the food markets can be traced to commodities deregulation in the US, which allowed for rampant speculation, as well as ethanol fuel mandates which promoted the inefficient conversion of food into fuel (Lagi, Bertrand and Bar-Yam 2011a;Merchant 2014;Lagi et al 2011b). Similar policy decisions in the US precipitated the 2008 economic crisis, as well as other market crashes (Harmon et al 2011;Harmon et al 2010).…”
Section: Global Systemsmentioning
confidence: 99%
“…Recent global crises, including the global financial crisis, the global food crisis, social unrest including the Arab Spring, and the Ebola epidemic and other pandemics, have demonstrated that global connectivity leads to vulnerabilities due to the high rate of global travel, and the rapid propagation of economic and social influences (Lagi, Bertrand and Bar-Yam 2011a;Merchant 2014;Lagi et al 2011b;Harmon et al 2011;Harmon et al 2010;Rutherford et al 2014;Rauch and Bar-Yam 2006). Many of the key problems today have to do with 'indirect effects' of human activities that may have substantial destructive effects on the human condition.…”
mentioning
confidence: 99%
“…Taking its cue from Lagi et al (2011) who link the outbreak of social unrest to changing food prices, the figure connects the outbreak of social unrest to relative income and profitability within the US agri-food sector. More specifically, the solid line tracks the average net income to sales ratio of the agricultural commodity traders relative to the average net income to sales ratio of the top 500 largest corporations listed in the United States; the duplex line traces the relative income of Midwestern farmers; and finally, the dotted lines rising from the chart's x-axis indicate the beginning dates of the major 'food riots' and revolts of the early twenty-first century.…”
Section: Rule Ambiguity: the Contested Boundary Between Hedging And Smentioning
confidence: 99%
“…Cargill quarterly net income data from Factiva database and Cargill (2016). Revolt data from Lagi et al (2011). For Midwestern farmers relative income data see Table 1.…”
Section: Rule Ambiguity: the Contested Boundary Between Hedging And Smentioning
confidence: 99%